PENGEMBANGAN SISTEM PERKULIAHAN KOMPETENSI DI PERGURUAN TINGGI AGAMA ISLAM - Lias Hasibuan (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2008)
Abstract: The Development Competency Learning Based System in Islamic Religious Higher Learning. Classroom learning activities will be effective if such process is undertaken in a comprehensive approach system. This paper is an attempt to discuss twelve learning process that have to be fulfilled in such learning activities. The author argues that fail to meet such requirement the expected learning system will be ineffective in building competency values as required in Islamic religious higher learning curriculum which is currently adapts to competency based system.Kata Kunci: sistem perkuliahan, kompetensi, PTAI